Evidence of ineffectiveness of insulin-like growth factor 1 (IGF-1) on in vitro production of bovine embryos: systematic review and meta-analysis - de Santi Phelippe Nunes, Giovana; Giroto, Alan Brunholi; Nunes, Sarah Gomes [UNESP]; Mareco, Edson Assunção; Díaz-Fabregat, Beatriz [UNESP]; César de Souza Castilho, Anthony (Elsevier, 2025)
Unsatisfactory results of in vitro maturation (IVM) impair the development, survival and implantation of the embryo. Insulin-like growth factor 1 (IGF-1) is widely used in IVM, but its efficacy is controversial and consistent evidence is lacking. To investigate the efficacy of IGF-1 in IVM, we conducted a systematic review and meta-analysis on bovine oocytes competence and subsequent embryonic development. We structured the research question according to the PICO model: "Does IGF-1 enhance in vitro embryo production in cattle during maturation?" We consulted scientific databases such as PubMed/MEDLINE, Embase and Scopus. The assessment of the methodological quality of the selected articles, the risk of bias, was performed with SYRCLE® by two reviewers. Data analysis was performed with R software, the "META" package for meta-analysis, using the metabin function to assess data proportions and estimate random effects, and the forest function for graphical representation. Of the 43 articles evaluated, eight were included in the statistical analysis. The results of the meta-analysis showed no significant effect of IGF-1 on cleavage rate (OR = 1.28 [0.96; 1.71]; p > 0.05) and on blastocyst yield (OR = 0.88 [0.64; 1.22]; p > 0.05). In conclusion, although IGF-1 is a key protein for cell differentiation, its addition during IVM does not promote blastocyst development. Therefore, we propose novel strategies to increase the bioavailability of IGF-1 during IVM in cattle to potentially improve embryonic outcomes.